Aplicabilidade do código florestal em APPs fluviais urbanas: estudo na cidade de Marechal Cândido Rondon - PR - Führ, Josiane de Oliveira Medeiros (2015)
This survey, conducted in the city of Marechal Cândido Rondon-PR, aims to analyze the applicability of the Forest Code in urban areas. Through literature review, preparation and analysis of maps, field work and interviews it was found that real estate speculation, the unequal distribution of wealth and the overvaluation of the land push the needy population to occupy the valleys and other places listed in the Forest Code (law 12,651 / 12) and Permanent Preservation Areas (APP). In practice, the standards of code for the APPs have been widely disobeyed, both due to the proliferation of informal settlements, and the implementation of urban installment projects, a reality that is associated with serious environmental damage, such as siltation of bodies of water. It is observed also major contradictions in the rules governing the APPs between urban and environmental legislation, both federal and municipal level. This fact leads to the constant discussions on the inapplicability of the Forest Code in urban areas. In this context, one of the alternatives to be analyzed is the relaxation of the rules governing the APP, not with regard to the limits, but with regard to use. An effective solution is the implementation of linear parks, which stand out as the most suitable project to reconcile recreation, urban beautification, flood control and improved water quality. The linear park becomes, currently, a structuring alternative for the environmental programs in urban areas, being used as a tool for planning and management of marginal areas to water courses, seeking to combine both urban and environmental aspects and the legal requirements.The applicability of the Forest Code in urban areas still raises many questions. The main problem still lies in the fact that the new Forest Code, in its genesis, was not thought to be applied in cities. This means that there is a set of environmental issues related to urban factor which is still open, and sooner or later will require thinking and debate that results in specific legislation. Thus, the study aims to contribute to this controversial and this question by analyzing the changes introduced with the enactment of the new law that directly affects the quality of life of the urban population